An experimental and numerical analysis of the fire resistance of concrete elements incorporating ROBOVOID void formers. (January 2023) - Loh, Thomas W.; Stehle, John; Zhang, Guomin; Shi, Long; Nguyen, Kate T.Q.
Abstract: Disposal of plastic waste poses a significant scientific challenge due to its non-biodegradable properties, increasing volume of production, and low recycling rate. One potential solution is its' manufacture into void formers for use in concrete building elements. However, plastics soften and decompose when exposed to high temperature fire which poses a challenge for fire safety design and certification of construction elements. A combined experimental and numerical study is presented to determine the fire resistance of concrete building elements that incorporate a novel recycled plastic void former (ROBOVOID, US patent No. 11, 352, 789). Multiple experimental fire exposure tests are performed to determine fire resistance and assess thermally induced damage for various building elements incorporating ROBOVOID. The fire resistance of the voided elements increased as the concrete content increased, or the fire intensity or exposure duration decreased. A finite element model is presented that can predict the thermal response of the building elements when subject fire representative of the Australian Standard Bushfire Attack Level (AS 1530.8.1), Building-to-Building (AS 5113) and Fire Resistance Level (AS 1530.4) conditions. The analysis indicates that polymer-based void formers can be incorporated into concrete structures while maintaining a high level of fire resistance for a variety of fire conditions.